AUTHENTIC AND INVULNERABLE SERVICE IN CLOUD COMPUTING - R. Karthikeyan (International Journal of Modern Agriculture, 2020)
Cloud storage is a type of online storage which helps to store on multiple virtual servers, rather than being hosted on dedicated servers Since we have remote database it provides us security problems. So to maintain data integrity, proposed design consists of efficient methods that enable on-demand data correctness verification. In this paper, we put more focuses on the support of file-oriented cloud applications. The proposed system ensures effective security measures, utilizing the token pre-computation process and data encryption. Our security analysis shows that both internal and external attacks require exponential computational costs; that is, our scheme is computationally secure against these attacks. So, the distributed protocols for storage correctness assurance will be of very essential to gain robust and secure cloud storage systems. Therefore, the steps toward future cloud computing is flexible and cost-effective for organization used by reliable and secure cloud computing.